ENTREVISTA AO PROF. DR. JOSÉ AMARANTE SANTOS SOBRINHO - Simoes, Vivian Gregores Carneiro Leão; Procópio, Eliabe dos Santos; Amaro, Luis Eduardo Rodrigues (Revista InterteXto, 2021)
ENTREVISTA AO PROF. DR. JOSÉ AMARANTE SANTOS SOBRINHO